Hubungan Pola Asuh Orangtua Dengan Perilaku Bullying Pada Remaja Di MAN Model 1 Manado - Nur Ainie Rabiasa; Sri Wahyuni; Helly Katuuk (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Bullying behavior is an act of intimidation carried out repeatedly by the stronger party against the weak party, done deliberately. The negative impact of bullying can make a person's life lost. Parenting is the attitude and way parents prepare younger family members, including children, to make their own decisions and act on their own. The purpose of the study was to determine whether or not there is a relationship between parenting style and bullying behavior in adolescents in MAN Model 1 Manado schools.This research method uses Cross Sectional approach. The sample was taken based on the number of respondents 49 people using simple random sampling. Data collection is carried out by means of questionnaires. Furthermore, the data that has been collected is processed using the help of the SPSS computer program to be analyzed with a spearman rank statistical test with a meaning level (α) of 0.05.The results showed that p = 0.596 was obtained compared to the α value = 0.05, where p≥α then H0 accepted H1 means that there is no relationship between parenting style and bullying behavior in adolescents at MAN Model 1 Manado school.The conclusion in this study was that there was no relationship between parenting style and bullying behavior in adolescents in MAN Model 1 Manado. Advice to adolescents is to increase empathy for others or the school environment and can exercise good restraint or manage emotions well so as not to cause aqqbehavioral attitudes that lead to bullying practices.